The Impact of Cholecystectomy After Endoscopic Sphincterotomy for Complicated Gallstone Disease. (October 2017) - Elmunzer, Joseph B; Noureldin, Mohamed; Morgan, Katherine A; Adams, David B; Coté, Gregory A; Waljee, Akbar K
Abstract : Objectives: Cholecystectomy after endoscopic sphincterotomy (ES) is associated with improved outcomes compared to ES alone, however randomized trials have included mainly fit surgical candidates. Our objective was to assess the impact of cholecystectomy after ES among elderly patients, in whom the perceived risks of surgery may be increased and the prevailing bias may be to defer cholecystectomy. Methods: We performed adjusted analyses comparing clinical outcomes in patients ≥65 years of age who did and did not undergo follow‐up cholecystectomy after endoscopic sphincterotomy for choledocholithiasis, ascending cholangitis, or gallstone pancreatitis. We also compared adverse events between the two groups. Results: In the ES alone group, 39.3% of patients experienced a recurrent complication compared with 18.0% in the ES and cholecystectomy group. After adjusting for comorbidities using multivariable regression, cholecystectomy in addition to ES was associated with a reduced risk of recurrent choledocholithiasis (OR 0.38, 95%CI 0.34–0.42, P <0.001), ascending cholangitis (OR 0.28, 95%CI 0.23–0.34, P <0.001), and gallstone pancreatitis (OR 0.35, 95%CI 0.24–0.49, P <0.001) compared to ES alone. This benefit was preserved after propensity score adjustment, in patients ≥75 years of age, and in those with major comorbidities including cancer, heart failure, and liver disease. Serious post‐operative complications such as myocardial infarction, pulmonary embolism, and pneumonia were not more common in the cholecystectomy group. Conclusions: Among older patients, including those with serious comorbidities, cholecystectomy after endoscopic sphincterotomy was associated with a significant and clinically important reduction in recurrent complications compared to sphincterotomy alone. This benefit did not appear to be outweighed by surgical complications, highlighting the importance of cholecystectomy, even in elderly patients whose lifespans may be limited by unrelated conditions.